Differentiating Branch Duct and Mixed IPMN in Endoscopically Collected Pancreatic Cyst Fluid via Cytokine Analysis. (25th December 2012) - Lee, Linda S.; Bellizzi, Andrew M.; Banks, Peter A.; Sainani, Nisha I.; Kadiyala, Vivek; Suleiman, Shadeah; Conwell, Darwin L.; Paulo, Joao A.
Abstract : Background . Differentiating branch duct from mixed intraductal papillary mucinous neoplasm (BD-IPMN) is problematic, but clinically important as mixed IPMNs are managed surgically, while some BD-IPMN may be followed. Inflammatory mediator proteins (IMPs) have been implicated in acute and chronic inflammatory and malignant pancreatic diseases. Aim . To compare IMP profile of pancreatic cyst fluid collected endoscopically from BD-IPMN and mixed IPMN. Methods . Pancreatic cyst fluid from ten patients (5 BD-IPMN and 5 mixed IPMN) was collected by endoscopic ultrasound-guided fine needle aspiration or endoscopic retrograde cholangiopancreatography. Concentrations of 89 IMPs in these samples were determined using a multiplexed bead-based microarray protein assay and compared between BD-IPMN and mixed IPMN. Results . Eighty-six of 89 IMPs were detected in at least one of the 10 samples. Fourteen IMPs were detected only in mixed IPMN, while none were only in BD-IPMN. Of these, TGF- β 1 was most prevalent, present in 3 of 5 mixed IPMNs. Seventy-two IMPs were detected in both BD-IPMN and mixed IPMNs. Of these, only G-CSF (P < 0.05 ) was present in higher concentrations in mixed IPMNs. Conclusion . TGF- β 1 and G-CSF detected in endoscopically collected pancreatic cyst fluid are potential diagnostic biomarkers capable of distinguishing mixed IPMN from BD-IPMN.